Downregulation of blood serum microRNA 29 family in patients with Parkinson’s disease - Xiaochen Bai (Nature Portfolio, 2017)
Abstract There is currently no reliable and easily applicable diagnostic marker for Parkinson’s disease (PD). The aims of the present study were to compare the expression profiles of the microRNA29 family (miR-29s) in blood serum from patients with PD with healthy controls and to clarify whether the expression of miR-29s is correlated with disease severity, duration or L-dopa therapy and whether expression depends on the gender and age of patients. The levels of blood serum miR-29s in 80 patients with PD and 80 unaffected controls were assessed by reverse transcription-quantitative real-time PCR. The PCR products were confirmed by cloning and sequencing. Additionally, the expression of miR-7 in the blood serum from PD patients and control subjects was assessed. Serum miR-29 levels were significantly downregulated in PD patients compared to healthy controls. The serum miR-29 levels in female PD patients were markedly higher than in male PD patients. The expression of serum miR-29a and miR-29c expression tended to decrease with disease severity. Moreover, we found that serum miR-7 levels did not differ between PD patients and control subjects. Therefore, the reduction of serum miR-29 levels, particularly miR-29a and miR-29c, warrants further investigation of its potential serving as biomarkers for PD.